Professional Activation of Persons with Disabilities in Germany, for Example, Young People Rehabilitated by the Federal Employment Agency - Beyersdorf , Joanna (Studia Oeconomica Posnaniensia, 2015)
In the German system of vocational rehabilitation, the Federal Employment Agency (BA) is responsible for the first vocational integration of adolescents with disabilities. Supporting self-determination and social integration of persons with disabilities is an important aim of German social policy, but it also results in considerable expenditure. Against this background, the author investigates the role of vocational activation measures in the process of young rehabilitants’ transition into the labour market. The data base is a survey of the Institute for Employment Research (IAB) of the BA, containing information on 1,961 adolescent rehabilitants. The method used is sequence analysis. The analysis yields six transition types, which differ from each other with respect to labour market attachment, individual health status and employment chances five years after leaving the general educational system. A considerable part of the sequence is characterized by the use of vocational education measures. As the author concludes, the transition process can be seen for this share of young vocational rehabilitants as a foundation for successful longer-term participation in the labour market. Another subgroup of young vocational rehabilitants eludes valuation, for their transition process is dominated by conditions not related to the structures of the labour market, nor to their health.